대학 인성교육으로서 ‘삶의 치유(Lebenstherapie) 프로그램’ 개발과 적용가능성 탐색 - 손승남(Son, Seung-Nam); 임배(Im, Bae) (교양교육연구, 2015)
본 연구의 목적은 대학생 삶의 치유(Lebenstherapie) 프로그램을 개발하고 대학의 인성교육에 이 프로그램을 적용하기 위한 가능성을 찾는 데 있다. 이를 위해서 문헌연구로 대학생 소진 현상과 관련 심리검사도구인 MBI와 KSCL95를 검토한 후 전인교육론과 인간도야이론을 기반으로 대학생 치유프로그램을 개발하였다. 이 프로그램은 대학생활에서 스트레스를 받고 소진된 학생들을 치유하기 위해 마련된 것이다. 치유프로그램 적용 시 고려할 사항은 다음과 같다. 첫째, 프로그램 적용의 시기와 장소는 최우선적으로 고려되어야 한다. 둘째, 잘 짜여진 운영진의 팀워크는 프로그램의 성공에 결정적이다. 셋째, 치유프로그램 구성 시 인지적 요소보다 신체적·정서적 요소를 우선시할 필요가 있다. 그 이유는 소진 대학생들이 신체적 강화를 통해 자신의 정신 건강을 향상시키고, 공감의 가치를 배울 수 있기 때문이다. 본 연구에서 제안한 프로그램은 궁극적으로 스트레스를 받고 소진된 학생들이 신체적· 정신적 건강을 회복하여 자신의 삶의 질을 향상시키는 데 도움을 줄 것이다. The purpose of this study was to develop a ‘Lebenstherapie’ as students healing program and to apply this program to university character education. In order to attain the goal it was supposed to use two psychological inventories such as the MBI and the KSCL 95. We also developed a students healing program ‘Lebenstherapie’ based on the holistic education, the german ‘Bildungstheory’ and the transpersonal psychology. This program can be conducted to heal stressed and burnout students. We suggested some considerations involved in the application of the healing program. Firstly the time and place of healing students should be considered as one of the most decisive factors. Secondly the teamwork as well as good planning may have a positive effect on the success of the program. Thirdly in making the healing program the physical and emotional components of the program need to be prioritized than the cognitive one. Because these students need help for enhancing their mental health through physical strengthening and learning the value of empathy. This program may help stressed and burnout students restore their physical and mental health and eventually contribute to the improvement of the quality of their lives. KCI Citation Count: 21